How technology shapes assessment design: Findings from a study of university teachers. (12th April 2016) - Bennett, Sue; Dawson, Phillip; Bearman, Margaret; Molloy, Elizabeth; Boud, David
Abstract: A wide range of technologies has been developed to enhance assessment, but adoption has been inconsistent. This is despite assessment being critical to student learning and certification. To understand why this is the case and how it can be addressed, we need to explore the perspectives of academics responsible for designing and implementing technology‐supported assessment strategies. This paper reports on the experience of designing technology‐supported assessment based on interviews with 33 Australian university teachers. The findings reveal the desire to achieve greater efficiencies and to be contemporary and innovative as key drivers of technology adoption for assessment. Participants sought to shape student behaviors through their designs and made adaptations in response to positive feedback and undesirable outcomes. Many designs required modification because of a lack of appropriate support, leading to compromise and, in some cases, abandonment. These findings highlight the challenges to effective technology‐supported assessment design and demonstrate the difficulties university teachers face when attempting to negotiate mixed messages within institutions and the demands of design work. We use these findings to suggest opportunities to improve support by offering pedagogical guidance and technical help at critical stages of the design process and encouraging an iterative approach to design.